Nominal or real? The impact of regional price levels on satisfaction with life - Thomas Deckers; Armin Falk; Hannah Schildberg-Hörisch (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We study the effect of real versus nominal income on life satisfaction. According to economic theory real income, i.e., nominal income adjusted for purchasing power, should be the relevant source of life satisfaction. Previous work, however, has only studied the impact of nominal income. We use a novel data set comprising about 7 million data points that are used to construct a price level for each of the about 400 administrative districts in Germany. We estimate a fixed effects model that controls for individual and local heterogeneity other than the price level. Our results show that higher price levels significantly reduce life satisfaction for individuals in the four lowest deciles of the income distribution. Furthermore, our findings suggest that people do not perceive money as neutral: the loss in life satisfaction caused by a higher price level is much larger than the loss in life satisfaction induced by a corresponding decrease in nominal income. Our results provide an argument in favor of regional indexation of government transfer payments such as social welfare benefits.
Keywords: D60; C23; D31; 330; life satisfaction; price index; neutrality of money; redistribution